(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT It is well- recognized for intellectuals that Sunnah is the second legislative source after the Holy Qur’an. Islamic nation is marked by its legislative system that follows and preserves what is left from its Prophet’s instructions. This study aims at highlighting obscure narrators in Musnad of Imam Ahmad, the Musnad of the tribes, by collecting the methods of each of selected hadiths in which there was a vagueness in order to enlighten the knowledge of the obscure narrator.